2013
DOI: 10.1016/j.ajog.2013.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Trends in venous thromboembolism among pregnancy-related hospitalizations, United States, 1994-2009

Abstract: OBJECTIVE-The purpose of this study was to evaluate national trends in the rate of pregnancyrelated hospitalizations for venous thromboembolism (VTE) from 1994-2009 and to estimate the prevalence of comorbid conditions among these hospitalizations.STUDY DESIGN-An estimated 64,413,973 pregnancy-related hospitalizations among women 15-44 years old were identified in the 1994-2009 Nationwide Inpatient Sample. Trends in VTEassociated pregnancy hospitalizations were evaluated with the use of variance-weighted least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 26 publications
6
54
1
3
Order By: Relevance
“…In several population-wide studies, women aged C 35 yr were observed to be at increased risk of pregnancy-related VTE compared with women aged \ 35 yr. [4][5][6] Advanced maternal age women 35-44 yr of age may also be at increased risk of postpartum VTE compared with women 15-24 yr of age. 25 Nevertheless, data from other studies suggest that this association should be questioned. In a Danish cohort study investigating pregnancy-associated VTE, maternal age was not associated with an increased risk of VTE, and no interaction was reported between maternal age and gestational age.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In several population-wide studies, women aged C 35 yr were observed to be at increased risk of pregnancy-related VTE compared with women aged \ 35 yr. [4][5][6] Advanced maternal age women 35-44 yr of age may also be at increased risk of postpartum VTE compared with women 15-24 yr of age. 25 Nevertheless, data from other studies suggest that this association should be questioned. In a Danish cohort study investigating pregnancy-associated VTE, maternal age was not associated with an increased risk of VTE, and no interaction was reported between maternal age and gestational age.…”
Section: Discussionmentioning
confidence: 92%
“…The median [IQR] ages of women were 38 [37][38][39][40][41] yr and 29 [25][26][27][28][29][30][31][32][33][34] yr in the AMA and non-AMA groups, respectively (Table 1). Other maternal demographic and obstetric characteristics were similar in both groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Relative to nonpregnant, reproductive age women, pregnant women have a 4-fold higher risk of VTE, 4 and postpartum risk is further increased, with estimates ranging from 9-fold to 84-fold higher. 4,5 Clinical guidelines addressing VTE risk and thromboprophylaxis aim to target high-risk populations to effectively prevent these complications. 6,7 However, the data on which guidelines have been developed rely on observational studies, extrapolation from other populations, and expert opinion.…”
Section: Hilary S Gammill University Of Washington; Fred Hutchinson mentioning
confidence: 99%